Mapping the Potential Distribution of Ticks in the Western Kanto Region, Japan: Predictions Based on Land-Use, Climate, and Wildlife - Doi, Kandai; Kato, Takuya; Tabata, Iori; Hayama, Shin-ichi (Insects (Basel, Switzerland), 2021)
Background: Tick distributions have changed rapidly with changes in human activity, land-use patterns, climate, and wildlife distributions over the last few decades. Methods: To estimate potential distributions of ticks, we conducted a tick survey at 134 locations in western Kanto, Japan. We estimated the potential distributions of six tick species (Amblyomma testudinarium Koch, 1844; Haemaphysalis flava Neumann, 1897; Haemaphysalis kitaokai Hoogstraal, 1969; Haemaphysalis longicornis Neumann, 1901; Haemaphysalis megaspinosa Saito, 1969; and Ixodes ovatus Neumann, 1899) using MaxEnt modeling based on climate patterns, land-use patterns, and the distributions of five common wildlife species: sika deer (Cervus nippon Temminck, 1838), wild boar (Sus scrofa Linnaeus, 1758), raccoon (Procyon lotor Linnaeus, 1758), Japanese raccoon dog (Nyctereutes procyonoides Gray, 1834), and masked palm civet (Paguma larvata C.E.H. Smith, 1827)). Results: We collected 24,546 individuals of four genera and 16 tick species. Our models indicated that forest connectivity contributed to the distributions of six tick species and that raccoon distribution contributed to five tick species. Other than that, sika deer distribution contributed to H. kitaokai, and wild boar distribution, bamboo forest, and warm winter climate contributed specifically to A. testudinarium. Conclusions: Based on these results, the dispersal of some tick species toward residential areas and expanded distributions can be explained by the distribution of raccoons and by forest connectivity.